Thermoplastic resin composition for electric / electronic packaging material and electric / electronic packaging material

JP2025029900AActive Publication Date: 2025-03-07TOYO INK MFG CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023134784
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-03-07
Estimated Expiration
2043-08-22

AI Technical Summary

Benefits of technology

【0016】 本発明により、面内バラつきなく塵やほこりの付着を防ぐことが可能な帯電防止性、成形時の残留応力や熱応力による変形を抑制できる成形性、製品の組み立てや使用時の摩擦や衝撃に耐えうる機械物性、低アウトガスや摩擦による汚染性がないクリーン性、および長時間の低吸水率の維持に優れた熱可塑性樹脂組成物、ならびに該熱可塑性樹脂組成物により形成される、電気電子包装材の提供が可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029900000001_ABST
    Figure 2025029900000001_ABST
Patent Text Reader

Abstract

To provide: a thermoplastic resin composition for electric / electronic packaging materials, which has excellent conductivity, no in-plane variation, and antistatic performance capable of preventing dust and dirt from sticking, and further which prevents long-term water absorption into a resin composition and is capable of forming a molded body with excellent moldability; and a molded body with excellent antistatic performance, which is formed of the thermoplastic resin composition.SOLUTION: There is provided a thermoplastic resin composition for electric / electronic packaging materials, which is a thermoplastic resin composition containing a carbon material and a thermoplastic resin. The carbon material contains a carbon nanotube (A1) and carbon black (A2). The thermoplastic resin contains a cycloolefin polymer (B1) and an elastomer (B2). The carbon nanotube (A1) satisfies (1) and (2). The thermoplastic resin composition has a difference ΔT of molding shrinkage factors of 0.10% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to thermoplastic resin compositions used to form packaging for electrical and electronic components, and to electrical and electronic packaging materials. [Background technology]

[0002] In recent years, office automation equipment and electronic devices have become smaller, lighter, more highly integrated, and more precise. If dust or dirt adheres to the electrical and electronic components used in these devices, it can cause problems such as poor contacts and reading errors. Therefore, it is necessary to minimize the adhesion of dust or dirt, and the requirements are becoming stricter as devices become smaller, lighter, more highly integrated, and more precise. IC chips and wafers used in semiconductors, and the internal parts of hard disks used in computers are prime examples of this. Usually, these parts are manufactured and assembled in so-called clean rooms where there is very little dust or dirt, but they are exposed to the outside air during transportation, and the adhesion of dust or dirt here can be a problem.

[0003] Therefore, electrical and electronic packaging materials used for transporting these electrical and electronic parts are also required to have high antistatic properties. Examples of electrical and electronic packaging materials include FOUPs (Front-Opening Unified Pods) and FOSBs (Front Opening Shipping Boxes) that safely and cleanly hold and transport silicon wafers, IC trays and embossed carrier tapes used to transport semiconductors such as IC chips, photomask cases that transport photomasks that serve as originals when transferring the circuit patterns of electronic components to an object to be transferred, and RSPs (Reticle SMIF Pods) that store reticles used in the front-end process of semiconductor manufacturing.

[0004] As thermoplastic resin compositions for forming electrical and electronic packaging materials used for storing or transporting such electrical and electronic components, Patent Document 1 discloses a thermoplastic resin composition using a polycarbonate resin and conductive carbon black, Patent Document 2 discloses a resin composition using an aromatic polycarbonate resin and carbon nanotubes, and Patent Documents 3, 4, and 5 disclose resin compositions using a cyclic olefin resin and carbon black, carbon fiber, or graphene. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-141130 A [Patent Document 2] JP 2010-155929 A [Patent Document 3] JP 2011-006534 A [Patent Document 4] JP 2013-231171 A [Patent Document 5] JP 2020-123720 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, it cannot be said that these conventional electrical and electronic packaging materials made from thermoplastic resin compositions have all the product performance properties, such as antistatic properties, high cleanliness, improved productivity, and moldability, which are sufficient to keep up with the recent trend toward smaller, lighter, more integrated, and more precise office automation equipment and electronic devices.

[0007] For example, as in Patent Document 1, when conductive carbon black and polycarbonate resin are used, the electrical resistance can be reduced by the carbon black, but in order to obtain high electrical conductivity and to achieve the generally required antistatic properties, a certain amount of carbon black alone is required to be added. This causes problems such as a decrease in mechanical strength such as impact resistance, a decrease in moldability, and a deterioration in appearance due to exposure of the carbon black. In addition, there is a large variation in electrical conductivity due to molding conditions and recycling, and further, the carbon black is detached due to wear during contact and friction, and the detached carbon black may adhere to electrical and electronic components such as IC chips, wafers, and internal parts of hard disks used in computers, causing malfunctions.

[0008] When carbon nanotubes are used as in Patent Document 2, there is a problem that when the carbon nanotubes are kneaded into a thermoplastic resin, the thickening effect of the carbon nanotubes reduces the fluidity of the thermoplastic resin composition, causing poor distribution and making it difficult to achieve uniform antistatic properties. Furthermore, in order to improve the antistatic performance, it is necessary to increase the content concentration of the carbon nanotubes, which causes problems such as an increase in water absorption, a decrease in impact resistance, and a decrease in moldability.

[0009] In Patent Documents 3, 4, and 5, a cyclic olefin resin, which has a lower water absorption rate than polycarbonate resin, is used as a resin to replace polycarbonate resin in order to improve the water absorption of electrical and electronic packaging materials. However, in this case, the molding shrinkage rate of the resin composition varies greatly depending on the characteristics of the contained conductive filler, and deformation may occur due to residual stress or thermal stress during molding, so moldability that can suppress such deformation is required.

[0010] In addition, among electrical and electronic packaging materials, FOUP, FOSB, photomask case, RSP, etc. are usually manufactured by forming a molded body using an injection molding machine or the like and fitting the obtained molded body. Therefore, the dimensions of the fitting part of the molded body in particular have a significant effect on the defect rate, contamination, and durability of the product when manufacturing the product. Furthermore, these electrical and electronic packaging materials may be required to have transparency or higher antistatic properties depending on the application, and may be manufactured by fitting molded bodies molded using thermoplastic resin compositions of different compositions, which requires higher moldability and high fit between the molded bodies.

[0011] On the other hand, even if a mold is designed in accordance with the molding shrinkage rate of each thermoplastic resin composition, deformation may occur due to residual stress or thermal stress during molding due to differences in the molding shrinkage rates of the thermoplastic resins, which may cause deterioration in the fit-up ability or deterioration in the cleanliness or durability of the product after fit-up.

[0012] In addition, in the process of using electrical and electronic packaging materials, washing and drying processes are often repeated, and it is highly necessary to maintain the electrical and electronic packaging materials in a dry state. However, since the material itself in the thermoplastic resin composition has a high water absorption rate, the time during which low humidity can be maintained is short, and the manufacturing cost increases, which is also a problem. Even when carbon fiber is used instead of carbon black to increase antistatic properties, the carbon fiber content must be increased, which causes problems with moldability such as an increase in water absorption rate and warping of molded products.

[0013] The need for electrical and electronic packaging materials to be kept dry is an example of the need for packaging materials such as FOUPs, FOSBs, and SMIPPODs to be used for transporting semiconductors. The packaging materials must be washed before and after use, but if moisture comes into contact with the wafers placed inside, it can react with the moisture and cause the wafer surface to become oxidized or stained (watermarked), so the packaging materials must be thoroughly dried. If the thermoplastic resin composition and the electrical / electronic packaging material have a low water absorption rate, there is no need to apply heat for drying before or after molding the electrical / electronic packaging material, and deformation and unnecessary thermal deterioration after molding can be prevented, and dimensions can be stabilized. In addition, the drying time of the washed electrical / electronic packaging material can be shortened and unnecessary thermal deterioration can be prevented, so that costs such as electricity bills can be reduced.

[0014] Therefore, an object of the present invention is to provide a thermoplastic resin composition that is excellent in antistatic properties, moldability, mechanical properties, and cleanability, and that can maintain a low water absorption rate for a long period of time, as well as an electrical and electronic packaging material formed from the thermoplastic resin composition. A further object of the present invention is to provide a thermoplastic resin composition having high interfitting properties. [Means for solving the problem]

[0015] That is, the present invention includes the following embodiments, but the embodiments of the present invention are not limited to the following. [1] A thermoplastic resin composition comprising a carbon material and a thermoplastic resin, The carbon material includes carbon nanotubes (A1) and carbon black (A2), The thermoplastic resin includes a cycloolefin polymer (B1) and an elastomer (B2), The carbon nanotube (A1) satisfies the following (1) and (2): The thermoplastic resin composition is characterized in that the molding shrinkage difference ΔT represented by the following formula (I) is 0.10% or less: Thermoplastic resin composition for electrical and electronic packaging materials. Formula (I) ΔT=|T 1 -T 0 | (In formula (I), T 1 is the molding shrinkage rate (%) when the thermoplastic resin composition is injection molded, T 0 is the mold shrinkage rate (%) when the cycloolefin polymer (B1) is injection molded. (1) The average diameter is 1 to 50 nm. (2) 1560-1600 cm in the Raman spectrum -1 Maximum peak intensity G in the range of 1310-1350 cm -1 The ratio of the maximum peak intensity D within this range (G / D ratio) is 0.5 to 2.0. [2] The thermoplastic resin composition for electrical and electronic packaging materials according to [1], wherein the total content of the carbon nanotubes (A1) and the carbon black (A2) is 13 mass% or less, based on 100 mass% of the thermoplastic resin composition. [3] The thermoplastic resin composition for electrical and electronic packaging materials according to [1] or [2], wherein the content of the elastomer (B2) is 4 mass% or less, based on 100 mass% of the thermoplastic resin composition. [4] The thermoplastic resin composition for electrical and electronic packaging materials according to any one of [1] to [3], wherein the elastomer (B2) is at least one of an olefin-based elastomer and a styrene-based elastomer. [5] Carbon black (A2) has a BET specific surface area of ​​1000 m 2 The thermoplastic resin composition for electrical and electronic packaging materials according to any one of [1] to [4], wherein the viscosity is 100 / g or less. [6] The thermoplastic resin composition for electrical and electronic packaging materials according to any one of [1] to [5], wherein the cycloolefin polymer (B1) has a tensile break strain of 5% or more. [7] A multipurpose test piece type A is molded from a thermoplastic resin composition in accordance with ISO3167, and then processed in accordance with ISO2818 to obtain a notched molded body. The Charpy impact strength measured in accordance with ISO179-1 is 2.0 kJ / m 2 The thermoplastic resin composition for electrical and electronic packaging materials according to any one of [1] to [6] above. [8] The thermoplastic resin composition for electrical and electronic packaging materials according to any one of [1] to [7], wherein a molded article having a thickness of 3 mm formed using the thermoplastic resin composition has a maximum surface height Sz of 50 μm or less. [9] An electrical / electronic packaging material formed from the thermoplastic resin composition for electrical / electronic packaging materials according to any one of [1] to [8].

[10] Surface resistivity is 1×10 4~1×10 12 The electrical and electronic packaging material according to [9], having a resistance of Ω / □. Effect of the Invention

[0016] The present invention makes it possible to provide a thermoplastic resin composition that has excellent antistatic properties that can prevent the adhesion of dust and dirt without in-plane variation, moldability that can suppress deformation due to residual stress and thermal stress during molding, mechanical properties that can withstand friction and impact during product assembly and use, cleanliness that is free from contamination due to low outgassing and friction, and the ability to maintain low water absorption for a long period of time, as well as an electrical and electronic packaging material formed from the thermoplastic resin composition.

[0017] Furthermore, by making it possible to provide a thermoplastic resin composition with high interlocking properties, it is expected that the composition will be used in a wide variety of electrical and electronic packaging materials, including FOUPs, FOSBs, photomask cases, and RSPs, which often require interlocking after molding. [Brief description of the drawings]

[0018] [Figure 1] FIG. 13 is a measurement concept diagram showing a method for evaluating fitability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention will be described in detail below. Furthermore, in this specification, a numerical range specified using "to" is intended to include the numerical values ​​before and after "to" as the lower and upper limit values ​​of the range. "Carbon nanotubes" are sometimes referred to as "CNT," "carbon black" as "CB," and "thermoplastic resin composition for electrical and electronic packaging materials" as "thermoplastic resin composition." Moreover, the term "main component" refers to the component that is blended in the largest amount among the components. Unless otherwise noted, the various components appearing in this specification may be used independently as a single type or as a combination of two or more types. The numerical values ​​specified in this specification are values ​​determined by the methods disclosed in the embodiments or examples. In the present invention, Tg is a value measured by a differential scanning calorimeter (DSC).

[0020] <<Thermoplastic resin composition for electrical / electronic packaging materials>> The thermoplastic resin composition of the present invention is used for forming a packaging material for electric and electronic components (referred to as electric and electronic packaging material), and contains a carbon material and a thermoplastic resin, the carbon material contains carbon nanotubes (A1) and carbon black (A2), the thermoplastic resin contains a cycloolefin polymer (B1) and an elastomer (B2), the carbon nanotubes (A1) satisfy the following (1) and (2), and a molding shrinkage difference ΔT represented by the following formula (I) is 0.10% or less. Formula (I) ΔT=|T1-T0| (In formula (I), T1 is the molding shrinkage rate (%) when the thermoplastic resin composition is injection molded, T0 is the molding shrinkage rate (%) when the cycloolefin polymer (B1) is injection molded. (1) The average diameter is 1 to 50 nm. (2) 1560-1600 cm in the Raman spectrum -1 Maximum peak intensity G in the range of 1310-1350 cm -1 The ratio of the maximum peak intensity D within this range (G / D ratio) is 0.5 to 2.0.

[0021] The molding shrinkage rate in the present application is a value calculated from the mold dimensions and the dimensions of the obtained molded article according to the following formula (II). Formula (II) Molding shrinkage rate (T) (%) = 100 × (mold size - molded product size) / mold size

[0022] Therefore, T1 can be determined from a molded article obtained by injection molding a thermoplastic resin composition, and T0 can be determined from a molded article obtained by injection molding the cycloolefin polymer (B1).

[0023] Specifically, for example, a dumbbell-shaped test piece as described in JIS K7139 is prepared using an injection molding machine, and the molding shrinkage rate can be determined in accordance with JIS K7152-4.

[0024] By keeping the mold shrinkage difference ΔT at 0.10% or less, it is possible to achieve both antistatic properties and moldability, and cleanliness and durability can be improved, and further, the fit is excellent when used as a container for storing or transporting electric and electronic components. From the viewpoints of antistatic properties, durability, and cleanliness, the mold shrinkage difference ΔT is preferably closer to 0, and ΔT is preferably 0 to 0.09%, and more preferably 0 to 0.06%. When the cycloolefin polymer (B1) is a mixture, the molding shrinkage difference ΔT can be found by taking the molding shrinkage of the cycloolefin polymer after mixing as T0.

[0025] The thermoplastic resin composition of the present invention uses carbon nanotubes (A1), carbon black (A2), cycloolefin polymer (B1), and elastomer (B2) whose molding shrinkage difference ΔT satisfies the above requirement and whose average diameter and G / D ratio in Raman spectrum are within specific ranges, and thus can be an excellent thermoplastic resin composition that has high moldability, excellent antistatic properties capable of preventing adhesion of dirt and dust without in-plane variation, mechanical properties capable of withstanding friction and impact during product assembly and use, high cleanliness with no contamination due to low outgassing or friction, and can maintain low water absorption for a long period of time.

[0026] <Carbon materials> The thermoplastic resin composition of the present invention contains carbon nanotubes (A1) and carbon black (A2) as carbon materials.

[0027] The total content of the carbon nanotubes (A1) and the carbon black (A2) is preferably 13% by mass or less based on 100% by mass of the thermoplastic resin composition. From the viewpoint of molding shrinkage rate and electrical conductivity, it is more preferably 3 to 10% by mass. If the content is too small, it may be difficult to satisfy antistatic properties, so it is preferably 3% by mass or more. If it is 13% by mass or less, it is preferable because moldability and water absorption are better.

[0028] The carbon nanotubes (A1) and the carbon black (A2) are preferably the main components of the carbon material. The total content of the carbon nanotubes (A1) and the carbon black (A2) in 100% by mass of the carbon material may be 100% by mass, and is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more.

[0029] (Carbon nanotubes (A1)) The carbon nanotubes (A1) satisfy the following (1) and (2). (1) The average diameter is 1 to 50 nm. (2) 1560-1600 cm in the Raman spectrum -1 Maximum peak intensity G in the range of 1310-1350 cm -1 The ratio of the maximum peak intensity D within this range (G / D ratio) is 0.5 to 2.0.

[0030] Carbon nanotubes have a structure similar to a graphene sheet rolled into a cylinder, and when they are single-walled they are called single-walled carbon nanotubes (SWCNT), and when they are multi-walled they are called multi-walled carbon nanotubes (MWCNT), and each individual carbon nanotube can be seen with an electron microscope, etc. Carbon nanotubes form primary aggregates of carbon nanotube fibers, entangled or bundled primary aggregates, but primary aggregates can also aggregate to form secondary or higher aggregates.

[0031] [Average diameter] From the viewpoint of antistatic properties and moldability, the carbon nanotubes (A1) have an average diameter of 1 to 50 nm. It is preferably 5 nm or more. It is also preferably 20 nm or less. If the average diameter is less than 1 nm, dispersion becomes difficult, and it becomes impossible to maintain sufficient antistatic properties while maintaining good moldability by maintaining the molding shrinkage rate. If the average diameter exceeds 50 nm, moldability and water absorption also deteriorate.

[0032] [G / D ratio of Raman spectrum] Carbon nanotubes (A1) have a Raman spectrum of 1560 to 1600 cm -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1 When the maximum peak intensity within this range is defined as D, the G / D ratio is 0.5 to 2.0, preferably 0.6 to 1.0. -1 The Raman shift seen around 1350 cm is called the G band of graphite. -1 The Raman shift seen around this band is called the D band, which is derived from defects in amorphous carbon and graphite. The higher the G / D ratio of a carbon nanotube, the higher the degree of graphitization. If the G / D ratio is less than 0.5, the amount of amorphous carbon nanotubes increases, which reduces the antistatic performance of the carbon nanotube. If the G / D ratio is greater than 2.0, the high crystallinity of the carbon nanotube reduces its dispersibility in the resin, which results in reduced antistatic performance.

[0033] The G / D ratio was measured by placing a powder sample in a microscopic laser Raman spectrophotometer (JASCO Corporation NRS-3100) and using a laser wavelength of 532 nm. -1 The G band from the graphite structure near 1350 cm -1 It can be calculated from the integral value of the D band peak derived from structural defects in the vicinity.

[0034] [Volume resistivity] Furthermore, the carbon nanotube (A1) has a volume resistivity of 1.2×10 -4 ~1.5×10-2 It is preferable that the volume resistivity is 1.0×10 -3 ~1.0×10 -2 It is more preferable that the volume resistivity of the carbon nanotube (A1) is within the above range, the antistatic property is improved. -2 A resistivity of Ω·cm or less is preferable because it allows for sufficient antistatic performance to be imparted while maintaining good fluidity. The volume resistivity can be measured using a powder resistivity measuring device (Loresta GP Powder Resistivity Measuring System MCP-PD-51, manufactured by Mitsubishi Chemical Analytech Co., Ltd.).

[0035] [Bulk density] The carbon nanotubes (A1) preferably have a bulk density of 0.002 to 0.5 g / mL, more preferably 0.005 to 0.2 g / mL. When carbon nanotubes having a bulk density in the above range are used, the dispersibility in the thermoplastic resin is improved, and the productivity during kneading can be improved.

[0036] The bulk density referred to here is the ratio of the mass of the sample to the volume of the container, which is measured using a Scott Volume Meter (manufactured by Tsutsui Rikagaku Kiki Co., Ltd.) as the measuring device, pouring carbon nanotube powder into a cylindrical container from the top of the measuring device, and measuring the mass of a certain volume of sample that has been leveled off at the point where it has become heaped, and is a value calculated based on the following formula (III). Formula (III) Bulk density (g / mL) = (Mass of the carbon nanotubes at a certain volume (g)) ÷ (Volume of the container (mL))

[0037] The carbon nanotube (A1) may be a single-walled carbon nanotube, a multi-walled carbon nanotube wound with two or more layers, or a mixture of these, but from the standpoint of cost and strength, multi-walled carbon nanotubes are preferred. Also, carbon nanotubes whose sidewalls have an amorphous structure instead of a graphite structure may be used.

[0038] Carbon nanotubes (A1) can generally be produced by laser ablation, arc discharge, chemical vapor deposition (CVD), combustion, etc., but any method may be used. In particular, the CVD method is a method for inexpensively and mass-producing carbon nanotubes by contacting fine catalyst particles, which are formed by supporting a metal catalyst such as iron or nickel on a support such as silica, alumina, magnesium oxide, titanium oxide, silicate, diatomaceous earth, alumina silica, silica titania, or zeolite, with a carbon-containing gas as a raw material, at a high temperature of usually 400 to 1000°C, and is preferable as a method for producing carbon nanotubes used in the present invention.

[0039] The content of the carbon nanotubes (A1) is not particularly limited, but from the viewpoints of productivity, antistatic properties, moldability, cleanliness, and water absorption, it is preferably 1% by mass or more, more preferably 2% by mass or more, based on 100% by mass of the thermoplastic resin composition, and is preferably 5% by mass or less, more preferably 4% by mass or less.

[0040] (Carbon Black (A2)) Carbon black (A2) is an amorphous carbon having electrical conductivity, and can be produced by incomplete combustion of oil or gas, or pyrolysis of hydrocarbons. The role of carbon black (A2) in the present invention is to form an electrical conductive path between the surface of the carbon nanotubes (A1) incorporated inside the molded body after injection molding or extrusion molding. When a molded body is produced by injection molding, a conductive resin composition containing only carbon nanotubes (A1) as a conductive material may not exhibit electrical conductivity even if the carbon nanotubes are sufficiently dispersed in the composition. The reason for this is thought to be that a layer (so-called "skin layer") with a high resin content and a low carbon nanotube (A1) concentration is formed on the surface of the molded body. In other words, when a resin composition contains a portion having a high resin content and a low concentration of carbon nanotubes (A1) and a portion having a low resin content and a high concentration of carbon nanotubes (A1), the viscosity of each portion when melted (melt viscosity) differs. For example, when injection molding is performed, the portion having a high content of resin with low viscosity and high fluidity is extruded first during molding, and the surface of the molded body is covered with a skin layer, which is thought to reduce the electrical conductivity of the molded body.

[0041] On the other hand, since carbon black (A2) generally has a lower specific surface area and oil absorption compared to carbon nanotubes (A1), a resin composition containing carbon black (A2) is less likely to have a high melt viscosity and form a skin layer on the surface of a molded article than a resin composition containing only carbon nanotubes (A1). In addition, since carbon black (A2) has a good affinity with carbon nanotubes (A1), even if carbon nanotubes (A1) are incorporated inside the molded article, a conductive path can be formed between carbon black (A2) present on the surface of the molded article, and the molded article of the present invention can exhibit high electrical conductivity.

[0042] As the carbon black (A2), various types of carbon black can be used alone or in combination, such as furnace black produced by continuously pyrolyzing a gaseous or liquid raw material in a reactor, ketjen black, particularly made from ethylene heavy oil, channel black, which is produced by burning a raw material gas and quenching it by applying the flame to the bottom surface of a channel steel, thermal black, which is obtained by periodically repeating combustion and pyrolysis of a gas as a raw material, and acetylene black, particularly made from acetylene gas as a raw material. Conventionally oxidized carbon black and hollow carbon can also be used.

[0043] The BET specific surface area of ​​carbon black (A2) is 1000m 2 / g or less, and more preferably 10 to 800m 2 / g, more preferably 10 to 500m 2 The BET specific surface area refers to the specific surface area measured by the BET method using nitrogen adsorption, and this BET specific surface area corresponds to the surface area of ​​carbon black. By setting the BET specific surface area in this range, the dispersibility of carbon black (A2) in the thermoplastic resin composition can be further improved.

[0044] The DBP oil absorption of carbon black (A2) is preferably 100 to 300 mL / 100 g, more preferably 100 to 200 mL / 100 g. When the DBP oil absorption is within the range of 100 to 300 mL / 100 g, the dispersibility of carbon black (A2) in thermoplastic resins can be further improved. The DBP oil absorption indirectly quantifies the structure of carbon black by measuring the void volume, and is a value measured in accordance with JIS K6217-4. "DBP" is an abbreviation for dibutylphthalate.

[0045] The primary particle size of the carbon black (A2) is preferably 0.005 to 1 μm, more preferably 0.01 to 0.2 μm, from the viewpoints of dispersibility and electrical conductivity. The primary particle size here is the average value of 20 particles measured with an electron microscope or the like.

[0046] Examples of commercially available carbon black include furnace blacks manufactured by Shin-Nichika Carbon Co., Ltd., such as Niteron #10, #200, and #300; furnace blacks manufactured by Tokai Carbon Co., Ltd., such as Toka Black #4300, #4400, #4500, and #5500; furnace blacks manufactured by Degussa Corporation, such as Printex L; furnace blacks manufactured by Columbian Co., Ltd., such as Raven 7000, 5750, 5250, 5000ULTRAIII, 5000ULTRA, Conductex SCULTRA, 975ULTRA, PUERBLACK 100, 115, and 205; and furnace blacks manufactured by Columbian Co., Ltd., such as #2350, #2400B, #2600B, #30050B, #3030B, #3200B, #3250 ... Examples of furnace blacks include, but are not limited to, furnace blacks manufactured by Mitsubishi Chemical Corporation such as #30B, #3350B, #3400B, and #5400B; furnace blacks manufactured by Cabot Corporation such as MONARCH1400, 1300, 900, VulcanXC-72R, and BlackPearls2000; furnace blacks manufactured by TIMCAL Corporation such as Ensaco250G, Ensaco260G, Ensaco350G, and SuperP-Li; ketjen blacks manufactured by Akzo Corporation such as Ketjen Black EC-300J and EC-600JD; and acetylene blacks manufactured by Denki Kagaku Kogyo Co., Ltd. such as Denka Black HS-100 and FX-35.

[0047] The content of carbon black (A2) is not particularly limited, but from the viewpoints of productivity, electrical conductivity, and moldability, it is preferably from 2 to 8 mass%, and more preferably from 3 to 6 mass%, based on 100 mass% of the thermoplastic resin composition.

[0048] <Thermoplastic resin> The thermoplastic resin composition of the present invention contains, as thermoplastic resins, a cycloolefin polymer (B1) and an elastomer (B2).

[0049] The total content of the cycloolefin polymer (B1) and the elastomer (B2) is preferably 87% by mass or more, more preferably 90% by mass or more, based on 100% by mass of the thermoplastic resin composition. From the viewpoint of low water absorption and outgassing, it is preferably 97% by mass or less. If the content is too low, the moldability may deteriorate, and if it is 87% by mass or more, the moldability and water absorption are better, which is preferable.

[0050] It is preferable that the cycloolefin polymer (B1) and the elastomer (B2) are the main components of the thermoplastic resin. The content of the cycloolefin polymer (B1) and the elastomer (B2) in the thermoplastic resin in the total of 100% by mass may be 100% by mass, and is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more.

[0051] (Cycloolefin polymer (B1)) The cycloolefin polymer (B1) may be an addition polymer of a cyclic olefin or a cyclic diene, or a hydrogenated product thereof, and is not particularly limited as long as it is a resin that can be molded by heating and melting. The cycloolefin polymer (A) may be a cycloolefin copolymer. In this specification, even if it is a cycloolefin polymer, if it is an elastomer, it is defined as an elastomer (B2).

[0052] As the cycloolefin polymer, a polymer obtained by ring-opening polymerization and hydrogenation of a cycloolefin monomer capable of ring-opening polymerization, such as norbornenes or cyclotetradodecenes, is preferably used. Specifically, for example, ZEONEX (registered trademark) or ZEONOR (registered trademark) manufactured by Zeon Corporation can be used.

[0053] As the cycloolefin copolymer, a copolymer made from norbornenes and olefins such as ethylene, or a copolymer made from tetracyclododecenes and olefins such as ethylene, is preferably used. Specifically, for example, APEL (registered trademark) manufactured by Mitsui Chemicals Inc. or TOPAS (registered trademark) manufactured by Ticona can be used.

[0054] The weight average molecular weight of the cycloolefin polymer (B1) is preferably from 3,000 to 500,000, more preferably from 8,000 to 200,000, from the viewpoints of versatility and mechanical properties. The weight average molecular weight is a value measured by gel permeation chromatography (GPC method) (a measured value obtained using isoprene as a standard substance and cyclohexane as an eluent).

[0055] The glass transition temperature (Tg) of the cycloolefin polymer (B1) varies depending on the type of monomer, the ratio of comonomer in copolymerization, the molecular weight, the hydrogenation rate, etc., but in the present invention, from the viewpoint of moldability and impact resistance when used as an electric / electronic packaging material, it is preferably 30°C to 300°C, more preferably 50°C to 200°C.

[0056] The melt flow rate (MFR) of the cycloolefin polymer (B1) is preferably 1 to 100 g / 10 min, more preferably 5 to 80 g / 10 min, from the viewpoints of moldability and impact resistance when used as an electric / electronic packaging material. In the present invention, the melt flow rate (MFR) is a melt flow rate value measured at 280° C. under a load of 2.16 kgf according to JIS K7210.

[0057] The tensile strain at break of the cycloolefin polymer (B1) is preferably 5% or more, more preferably 8%, and is preferably 200% or less, more preferably 100% or less. By keeping it in this range, the durability, moldability, and fitability are improved when the resin composition is used as an electric / electronic packaging material. The tensile breaking strain (%) can be measured in accordance with JIS K7161.

[0058] The deflection temperature under load of the cycloolefin polymer (B1) is preferably 50°C or higher, more preferably 70°C to 200°C, from the viewpoints of moldability and impact resistance when used as an electric / electronic packaging material. In the present invention, the deflection temperature under load is the temperature at which the increase in bending strain becomes 0.2% when a load of 1.80 MPa is applied while gradually increasing the temperature at 120° C. / h in a three-point bending method.

[0059] The content of the cycloolefin polymer (B1) is not particularly limited, but from the viewpoints of low water absorption, outgassing, and moldability, it is preferably 80 to 95 mass%, and more preferably 83 to 90 mass%, based on 100 mass% of the thermoplastic resin composition.

[0060] (Elastomer (B2)) Elastomer means a polymeric substance that is elastic at room temperature (25℃), and may be a natural or synthetic polymeric substance, and mainly contributes to improving impact strength. Elastomers soften and become plastic when heated to an appropriate temperature, and become elastic when cooled, and do not show a melting point when measured by the DSC method.

[0061] The elastomer (B2) is not particularly limited as long as it is an elastomer, and examples thereof include olefin-based elastomers, styrene-based elastomers, and polyester-based elastomers. From the viewpoint of compatibility with the cycloolefin polymer (B1), and because the molded product has excellent mechanical properties, it is preferable to use an olefin-based elastomer or a styrene-based elastomer. Furthermore, an acid-modified elastomer may also be used.

[0062] An acid-modified elastomer refers to an elastomer into which an acidic functional group has been introduced by graft polymerization or the like. Suitable examples of the acid-modified elastomer include an acid-modified styrene-based elastomer and an acid-modified olefin-based elastomer. Acid modification refers to the introduction of a cyclic acid anhydride group or a carboxylic acid group into the copolymer side chain with, for example, a cyclic acid anhydride such as succinic anhydride, maleic anhydride, glutaric anhydride, or phthalic anhydride.

[0063] An olefin-based elastomer is a polymeric material that is obtained by polymerizing an olefin as a monomer, and is composed of carbon and hydrogen atoms, and is elastic at room temperature (25°C). As the monomer of the olefin-based elastomer, a copolymer of ethylene, propylene, or butene as a comonomer based on an olefin such as ethylene, propylene, or butene is preferable, and among them, an olefin-based elastomer having a low glass transition temperature is more preferable. The glass transition temperature (Tg) is preferably -100 to -10°C, more preferably -65°C to -50°C.

[0064] Examples of commercially available olefin-based elastomers that can be used include Sarlink (registered trademark) manufactured by Toyobo Co., Ltd., Thermorun (registered trademark) manufactured by Mitsubishi Chemical Corporation, and Tufmer (registered trademark) and Milastomer (registered trademark) manufactured by Mitsui Chemicals, Inc. Among them, Tufmer and Milastomer manufactured by Mitsui Chemicals, Inc. are preferred.

[0065] A styrene-based elastomer is a polymeric substance that has an aromatic ring in the main chain and is elastic at room temperature (25°C) and is obtained by polymerizing styrene-based monomers such as butadiene and butylene, and is typified by an aromatic vinyl-conjugated diene block copolymer. That is, as the styrene-based elastomer, styrene / butadiene / styrene (SBS), styrene / butadiene / butylene / styrene (SBBS), and styrene / ethylene / butylene / styrene (SEBS) are preferred, and among them, SEBS is more preferred from the viewpoint of compatibility. In addition, the elastomer may be acid-modified. Among the modified styrene-based elastomers, maleic acid-modified styrene-based elastomers are preferred.

[0066] Examples of commercially available styrene-based elastomers that can be used include Tufprene (registered trademark) and Tuftec (registered trademark) manufactured by Asahi Kasei Corporation, Kraton (registered trademark) manufactured by Kraton Polymer Japan Co., Ltd., Esporex SB (registered trademark) manufactured by Sumitomo Chemical Co., Ltd., Rabalon (registered trademark) manufactured by Mitsubishi Chemical Corporation, and Septon (registered trademark) manufactured by Kuraray Co., Ltd. Among these, Tuftec manufactured by Asahi Kasei Corporation is preferred.

[0067] From the viewpoints of moldability, water absorption, and impact resistance, the content of the elastomer (B2) is preferably 4% by mass or less, more preferably 3% by mass or less, based on 100% by mass of the thermoplastic resin composition. From the viewpoint of impact resistance, it is preferably 2% by mass or more. When the content of the elastomer (B2) is in this range, deterioration of moldability and water absorption, and generation of outgassing can be suppressed, which is preferable. Also, multiple types of elastomers may be used.

[0068] <Optional ingredients> If necessary, additives such as antistatic materials, e.g., carbon materials other than the carbon nanotubes (A1) and the carbon black (A2), weather resistance stabilizers, coupling agents, crystal nucleating agents, resin fillers, and colorants, e.g., dyes and pigments, may be added to the thermoplastic resin composition of the present invention for the purpose of improving the weather resistance, moldability, and productivity of the resin composition. Examples of antistatic materials include carbon materials such as carbon fiber, graphite, and graphene, metal particles, and ionic liquids. The content of the antistatic material other than the carbon nanotubes (A1) and the carbon black (A2) is preferably 10 mass % or less, and more preferably 5 mass % or less, based on the mass of the thermoplastic resin composition (100 mass %).

[0069] The thermoplastic resin composition preferably does not contain any volatile components. In 100% by mass of the thermoplastic resin composition, the amount of volatile components such as solvents and low molecular weight components is preferably 5% by mass or less, and more preferably 1% by mass or less.

[0070] <Method of producing thermoplastic resin composition> The method for producing the thermoplastic resin composition of the present invention is not particularly limited. For example, carbon nanotubes (A1), carbon black (A2), cycloolefin polymer (B1), elastomer (B2), and, if necessary, additives, etc. can be added and mixed in a Henschel mixer, tumbler, disper, etc., and then mixed or melt-kneaded in a batch kneader such as a kneader, roll mill, super mixer, Henschel mixer, Schuggie mixer, vertical granulator, high-speed mixer, Furmatrix, ball mill, steel mill, sand mill, vibration mill, attritor, or Banbury mixer, a twin-screw extruder, a single-screw extruder, or a rotor-type twin-screw kneader, to obtain a resin composition in the form of pellets, powder, granules, beads, or the like. In the present invention, it is preferable to use a twin-screw extruder or a single-screw extruder for melt kneading, and it is more preferable to use a twin-screw extruder from the viewpoint of dispersibility of the carbon material. When using a twin-screw extruder, the generation of outgas can be further suppressed, and the process can be excellent in cleanliness.

[0071] In the thermoplastic resin composition of the present invention, by using the carbon nanotubes (A1) and the carbon black (A2), the carbon nanotubes are uniformly distributed in the cycloolefin polymer (B1) and the elastomer (B2) by melt kneading, and a molded article with excellent antistatic properties and no in-plane variation can be formed.

[0072] [Surface roughness] The thermoplastic resin composition is preferably such that the maximum height Sz of the surface of the molded article is 50 μm or less when the molded article is formed into a 3 mm thick article. This is preferable because it provides the cycloolefin polymer (B1) with sufficient electrical conductivity and provides a molded article that can maintain moldability, impact resistance, and low water absorption. Furthermore, by suppressing water absorption into the thermoplastic resin composition, it is possible to form a molded article with better dimensional stability. The smaller the maximum height Sz, the more preferable, and it is more preferable that it is 30 μm or less.

[0073] The maximum height Sz of the surface of the molded product varies greatly depending on the dispersibility of the carbon nanotubes, and is important in terms of moldability, impact resistance, water absorption, and the like. In order to achieve this range, in addition to using the carbon nanotubes (A1), carbon black (A2), cycloolefin polymer (B1), and elastomer (B2) of the present invention, it is possible to control the carbon nanotubes by highly dispersing them depending on the type and amount of each, and the dispersion conditions during melt kneading of the resin to form the molded product. By using the carbon nanotubes (A1), carbon black (A2), cycloolefin polymer (B1), and elastomer (B2) of the present invention, it is possible to maintain electrical conductivity while maintaining low water absorption in addition to moldability and impact resistance. Furthermore, it is possible to form a molded product with a smooth surface and excellent antistatic performance without in-plane variation.

[0074] The method for forming a molded article for measuring the maximum height Sz of the molded article surface is not limited to any particular method, so long as it is possible to form a molded article having a thickness of 3 mm. For example, it can be molded and measured by the method described in the Examples. Specifically, for example, the thermoplastic resin composition for electrical and electronic packaging materials of the present invention can be heated and melted, and a molded article can be formed using an injection molding machine. A molded article having a thickness of 3 mm can be produced by using the injection molding machine at a temperature about 30° C. higher than the melting point of the cycloolefin polymer (B1).

[0075] The maximum height Sz of the surface of a molded article is a parameter that is a three-dimensional extension of the maximum height Rz, which is a two-dimensional roughness parameter, and represents the distance from the highest point to the lowest point on the measured surface. The maximum height Sz can be determined by measurement in accordance with ISO25178. When extracting a cross-section of a surface and discussing its roughness, Sz and Rz can be considered to be synonymous.

[0076] The maximum height Sz (μm) of the produced 3 mm thick molded body is determined using, for example, a Talysurf CCI MP-HS manufactured by Taylor / Hobson, with a measurement length of 2.5 mm x 2.5 mm and a robust Gaussian filter of 0.08 mm.

[0077] [Charpy impact strength] The thermoplastic resin composition was molded into a multipurpose test piece type A in accordance with ISO3167, and then processed in accordance with ISO2818 to obtain a notched molded body, which had a Charpy impact strength of 2.0 kJ / m2 or more as measured in accordance with ISO179-1. 2 This improves the fit when the electrical / electronic packaging material is molded, reducing the defective rate, and enables the material to withstand shocks when used as an electrical / electronic packaging material and to be used for a long period of time. The Charpy impact strength is set at 2.5 kJ / m from the viewpoint of fitting and durability. 2 More preferably, it is 45 kJ / m or more. 2 Less than 30 kJ / m is preferable. 2 The following is more preferred:

[0078] <Electrical and electronic packaging materials> The electrical / electronic packaging material of the present invention is a packaging material for electrical / electronic components, and is formed from a thermoplastic resin composition for electrical / electronic packaging materials. The electrical and electronic packaging material may be a molded article directly formed from the thermoplastic resin composition for electrical and electronic component packaging materials using a molding machine, or the electrical and electronic component packaging material may be formed by fitting and combining two or more molded articles obtained using a molding machine such as an injection molding machine or an extrusion molding machine. Since the thermoplastic resin composition of the present invention has high interlocking properties, even when the resulting electrical / electronic component packaging material, such as a container, is interlocked, it has excellent cleanliness and durability, and the product defect rate can be reduced.

[0079] The molded article can be obtained by melt mixing the compound or master batch, which is the thermoplastic resin composition, and the diluted resin in a molding machine usually set at 50° C. to 350° C., forming the shape of the molded article, and cooling it. The temperature of the molding machine does not matter as long as it is a temperature at which the thermoplastic resin softens, but it is preferably a temperature 30° C. or more higher than the softening point of the thermoplastic resin that is the main component.

[0080] Examples of the molding method that can be used include extrusion molding, injection molding, blow molding, compression molding, transfer molding, film molding such as T-die molding and inflation molding, calendar molding, spinning, etc. Injection molding is preferred because it can be molded into any shape.

[0081] The shape of the molded article is not particularly limited, and examples thereof include a plate, a rod, a fiber, a tube, a pipe, a bottle, a film, etc. Two or more of the obtained molded articles can be fitted together to form a packaging material for electric and electronic parts.

[0082] Examples of electric and electronic components include semiconductor-related components such as silicon wafers, hard disks, disk substrates, IC chips, magneto-optical disks, high-performance substrate glass for LCDs, LCD color filters, and magnetoresistive heads for hard disks; components for semiconductor production such as reticles; and components for electronic circuit production such as photomasks.

[0083] Electrical and electronic packaging materials are used for storing or transporting these electrical and electronic components, and by imparting electrical conductivity to the packaging material itself, they have antistatic properties, preventing the uneven distribution and accumulation of electrons due to friction, etc., and can prevent the accumulation of static electricity. Specific examples of electrical and electronic packaging materials include FOUPs (Front-Opening Unified Pods) and FOSBs (Front Opening Shipping Boxes) that safely and cleanly hold and transport silicon wafers, packaging materials used for semiconductor-related parts such as IC trays and embossed carrier tapes used to transport IC chips, photomask cases that transport photomasks that serve as originals when transferring the circuit patterns of electronic parts to the target, reticle transport containers that store reticles used in the front-end process of semiconductor manufacturing, and RSPs (Reticle SMIF Pods). FOUPs, FOSBs, photomask cases, and RSPs often require fitting, IC trays and inbossed carrier tapes often do not require mating. In particular, since the molded article formed from the thermoplastic resin composition of the present invention has excellent fitability, it can be suitably used as a material for containers obtained by fitting, specifically, it can be particularly suitably used as a material for FOUPs, FOSBs, photomask cases, RSPs, etc.

[0084] [Surface resistance value] Electrical and electronic packaging materials are required to have sufficient antistatic properties to minimize the adhesion of dust and dirt, and to accommodate the trend toward smaller, lighter, more integrated, and more precise office automation equipment and electronic devices. To achieve this, the surface resistance of electrical and electronic packaging materials must be within the antistatic range of 1×10, which is necessary from the standpoint of cleanliness, to protect electronic devices from static electricity damage and keep out dust and dirt to maintain a high level of cleanliness. 4 ~1×10 12 It is preferably in the range of Ω / □, and 1×10 6 ~1×10 10 It is more preferable that the resistance is in the range of Ω / □. Surface resistance is 1×10 12By having a resistance of Ω / □ or less, it is possible to suppress the charging of electronic devices due to the effect of frictional charging of electric and electronic components. Electronic devices that have accumulated static electricity can be damaged by the discharge of static electricity, or can electrostatically attract dust and dirt suspended in the air, causing problems, but this is preferable because it can prevent this. 4 By having a resistance of Ω / □ or more, it is possible to better prevent damage to electronic devices due to the strong current and high voltage generated during static electricity discharge caused by the charge moving too fast within electrical and electronic components. Among them, 1×10 6 ~1×10 10 When the range is Ω / □, the half-life of the electrostatic potential is significantly shortened, and excellent antistatic performance can be exhibited, which is preferable. EXAMPLES

[0085] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" means "parts by mass" and "%" means "% by mass".

[0086] The powder Raman spectroscopic analysis and average diameter of the carbon nanotubes, the BET specific surface area of ​​the carbon black, and the tensile breaking strain of the cycloolefin polymer were measured by the following methods.

[0087] <Powder Raman spectroscopy of carbon nanotubes> The carbon nanotubes were placed in a microscopic laser Raman spectrophotometer (JASCO Corporation NRS-3100) and measurements were performed using a laser wavelength of 532 nm. The measurement conditions were: acquisition time 60 seconds, number of integrations 2, neutral density filter 10%, objective lens magnification 20 times, confocus hole 500, slit width 100 μm, measurement wavelength 100 to 3000 cm -1 The carbon nanotubes for measurement were separated onto a slide glass and flattened using a spatula. -1 The maximum peak intensity in the range of G, 1310~1350cm-1 The maximum peak intensity within the range was defined as D, and the G / D ratio was defined as the G / D ratio of the carbon nanotube.

[0088] <Average diameter and fiber length of carbon nanotubes> The average diameter of the carbon nanotubes was measured by observing the carbon nanotubes with a scanning electron microscope (JSM-6700M, manufactured by JEOL) at an accelerating voltage of 5 kV and taking a 50,000-fold image (pixel count 1024 × 1280). Next, the short axis length and long axis length of each of 20 random carbon nanotubes in the taken image were measured, and the number average of the obtained short axis lengths was taken as the average diameter of the carbon nanotubes, and the number average of the obtained long axis lengths was taken as the fiber length of the carbon nanotubes.

[0089] <Volume resistivity of carbon nanotubes> The volume resistivity of the carbon nanotubes was measured using a powder resistivity measurement device (Mitsubishi Chemical Analytech Corp.: Loresta GP Powder Resistivity Measurement System MCP-PD-51) with a sample mass of 1.2 g and a powder probe unit (four-needle ring electrode, electrode spacing 5.0 mm, electrode radius 1.0 mm, sample radius 12.5 mm) with an applied voltage limiter of 90 V. The volume resistivity [Ω cm] of the conductive powder under various pressures was measured.

[0090] <Bulk density of carbon nanotubes> The bulk density of carbon nanotubes is measured using a Scott Volume Meter (manufactured by Tsutsui Rikagaku Kiki Co., Ltd.) by pouring carbon nanotube powder into a cylindrical container from the top of the measuring device, measuring the mass of a certain volume of sample that has been leveled off at the point where it has become heaped, and is the ratio of this mass to the container volume, and is a value calculated based on the following (Equation 2). (Equation 2) Bulk density (g / mL) = (Mass of the carbon nanotubes at a certain volume (g)) ÷ (Volume of the container (mL))

[0091] <BET specific surface area of ​​carbon black> 0.03 g of carbon black was weighed out using an electronic balance (MSA225S100DI, manufactured by Sartorius), and then dried for 15 minutes at 110° C. while degassing. Thereafter, the specific surface area of ​​the carbon black was measured using a fully automatic specific surface area measuring device (HM-model1208, manufactured by MOUNTECH).

[0092] <Tensile strain at break of cycloolefin polymer> The tensile breaking strain of the cycloolefin polymer was measured in accordance with JIS K7161 by preparing a dumbbell-shaped test piece as described in JIS K7139 (Plastics - Test Pieces) using an injection molding machine, and a tensile test was performed using a tensile testing machine (Shimadzu Corporation, Autograph AGS-H) to measure the breaking strain (%).

[0093] The materials used in the examples are as follows: <Carbon nanotubes (A1), etc.> (A1-1) CM-130 (Hanhwa Chemical Hanos Co., Ltd., average diameter 15 nm, fiber length 10 to 50 μm, G / D ratio 0.94, volume resistivity 2.0 × 10 -2 Ω cm, bulk specific gravity 0.03 (g / cc)) (A1-2) Flotube 7000 (CNano, average diameter 6 nm, fiber length 50-150 μm, G / D ratio 0.76, volume resistivity 1.5×10 -2 Ω cm, bulk specific gravity 0.007 (g / cc)) (A1-3) 0555CA (manufactured by Corefront Co., Ltd., average diameter 45 nm, fiber length 5 to 20 μm, G / D ratio 0.98, volume resistivity 2.0 × 10 -2 Ω cm, bulk specific gravity 0.06 (g / cc)) (A'1-1) VGCF-H (Showa Denko K.K., average diameter 150 nm, fiber length 5 μm, G / D ratio 7.23, volume resistivity 1.5 × 10 -2 Ω cm, bulk specific gravity 0.08 (g / cc))

[0094] <Carbon black (A2)> (A2-1) Denka Black (manufactured by Denka Co., Ltd., particle size 35 μm, DBP oil absorption 160 ml / 100 g, specific surface area 69 m 2 / g) (A2-2) Vulcan XC72 (Cabot Specialty Chemicals, Inc., particle size 30 μm, DBP oil absorption 173 ml / 100 g, specific surface area 254 m 2 / g) (A2-3) Ketjen Black EC300J (manufactured by Lion Specialty Chemicals Co., Ltd., particle size 40 μm, DBP oil absorption 365 ml / 100 g, specific surface area 800 m 2 / g)

[0095] <CNF(カーボンナノファイバー)> (A3-1) EPU-LCL (carbon fiber, manufactured by Nippon Polymer Co., Ltd., diameter 7 μm, fiber length 6 mm, volume resistivity 1.0 × 10 0 Ω cm)

[0096] <Cycloolefin polymer (B1)> (B1-1) ZEONOR1020R (manufactured by Zeon Corporation, tensile breaking strain 100%, Tg 105°C, deflection temperature under load 101°C, MFR 20g / 10 min, mold shrinkage 0.20%) (B1-2) ZEONOR1600R (manufactured by Zeon Corporation, tensile breaking strain 10%, Tg 163°C, deflection temperature under load 161°C, MFR 7g / 10 min, mold shrinkage 0.45%) (B1-3) APL6509T (Mitsui Chemicals), tensile break strain 6%, Tg 80°C, deflection temperature under load 70°C, MFR 30g / 10min, mold shrinkage 0.55%) (B1-4) TOPAS5013L-10 (Polyplastics, tensile breaking strain 2%, Tg 127°C, deflection temperature under load 134°C, MFR 48g / 10min, mold shrinkage 0.55%) The molding shrinkage of the cycloolefin polymer is a value determined by the method described later in the section on measuring molding shrinkage of a molded product.

[0097] <Elastomer (B2)> (B2-1) Toughmer PN2060 (Mitsui Chemicals, Inc., olefin-based elastomer) (B2-2) Tuftec H1221 (Asahi Kasei Corporation, styrene-based elastomer) (B2-3) Tuftec M1943 (Asahi Kasei Corporation, acid-modified styrene-based elastomer) (B2-4) Hytrel 5557 (Toray Celanese, polyester elastomer)

[0098] Example 1 (Production of Thermoplastic Resin Composition) 3 parts of carbon nanotubes (A1-1), 4 parts of carbon black (A2-1), 89 parts of cycloolefin polymer (B1-2), and 4 parts of elastomer (B2-1) were mixed and melt-kneaded, extruded at 240°C using a twin-screw extruder (manufactured by The Japan Steel Works, Ltd.), and granulated to obtain a thermoplastic resin composition.

[0099] (Examples 2 to 8, Comparative Examples 1 to 6) Thermoplastic resin compositions were obtained in the same manner as in Example 1, except that the materials and blending amounts (parts by mass) were changed to those shown in Table 1.

[0100] Example 9 3 parts of carbon nanotubes (A1-1), 4 parts of carbon black (A2-1), 89 parts of cycloolefin polymer (B1-2), and 4 parts of elastomer (B2-1) were mixed and melt-kneaded, extruded at 240°C using a single-screw extruder (manufactured by The Japan Steel Works, Ltd.), and granulated to obtain a thermoplastic resin composition.

[0101] <Measurement of molding shrinkage rate> The mold shrinkage of the obtained thermoplastic resin composition and cycloolefin polymer (B1) was determined by the following method, and the mold shrinkage difference ΔT represented by the formula (I) was calculated. The results are shown in Table 1. Formula (I) ΔT=|T 1 -T 0 | T 1 is the molding shrinkage rate (%) when the thermoplastic resin composition is injection molded T 0 is the mold shrinkage rate (%) when cycloolefin polymer (B1) is injection molded

[0102] The molding shrinkage rate of the molded body was calculated by the following method, using the thermoplastic resin composition or the cycloolefin polymer used in each thermoplastic resin composition, preparing a dumbbell-shaped test piece according to JIS K7139 (Plastics - Test piece) by setting the cylinder temperature of the injection molding machine to 270°C and the mold temperature to 95°C. (1) The test piece was left to stand at room temperature (23°C) for 24 hours, and then the dimensions were measured with a vernier caliper. Measurements were performed on three test pieces prepared under the same conditions, and the average value was taken as the molded body dimension (mm). (2) The mold was measured with calipers at room temperature, and the measured value was recorded as the mold dimension (mm). (3) Based on each value, the molding shrinkage rate (%) was calculated using formula (1). Formula (II) Molding shrinkage rate (T) (%) = 100 × (mold size - molded product size) / mold size The molding shrinkage rate of the molded product obtained by injection molding the thermoplastic resin composition is T 1 (%), and the molding shrinkage rate of the molded article obtained by injection molding the cycloolefin polymer (B1) used therein is T 0 (%).

[0103] [Table 1]

[0104] Measurement and evaluation of physical properties of thermoplastic resin compositions and molded articles The physical properties of the thermoplastic resin composition and the molded product were measured and evaluated by the following methods. The results are shown in Table 2.

[0105] <Measurement of maximum surface height Sz> The thermoplastic resin composition was injection molded using an injection molding machine with a cylinder temperature of 270° C. and a mold temperature of 95° C. to produce a molded body having dimensions of 90 mm length × 110 mm width × 3 mm thickness. The maximum height Sz (μm) of the flat surface of the obtained 3 mm thick molded body was measured using a Talysurf CCI MP-HS manufactured by Taylor / Hobson, with a measurement length of 2.5 mm x 2.5 mm and a robust Gaussian filter of 0.08 mm.

[0106] <Charpy impact strength> The thermoplastic resin composition was used to mold a multipurpose test piece type A (length 80 mm, width 10 mm, thickness 4 mm) in accordance with ISO 3167, and further processed in accordance with ISO 2818 to produce a molded body with a 2 mm notch. Using the obtained notched molded body, the Charpy impact strength was measured with a hammer capacity of 2 J in accordance with ISO179-1.

[0107] <Moldability evaluation> The moldability of the thermoplastic resin composition was evaluated based on the interfitting property. Using the thermoplastic resin composition, the cylinder temperature of the injection molding machine was set to 270° C., the mold temperature was set to 95° C., and 20 shots were used to mold test pieces 1 and 3 for evaluating fit shown in FIG. As shown in Figure 1, the moldability was evaluated by molding a test piece 1 for evaluating fitability, which has a fitting portion 2, and a test piece 3 for evaluating fitability, which has an insertion portion 1 cm wide, and by observing the breakage, cracks, and dislodging of the test pieces after fitting, etc., caused by insertion during fitting. The evaluation criteria are as follows: [Evaluation Criteria] ++ No extra force is required when mating There are zero defects such as breaks, cracks, or dislodgments when mated. (Excellent) + The number of defects such as breakage, cracks, or pullouts when mated is between 1 and 5. (Good) NG: The number of defects such as breaks, cracks, or dislodgments when mated is 5 or more.

[0108] <Water absorption> With reference to JIS K7209, the water immersion time was increased to 192 hours, and the water absorption test was carried out according to the following procedure. The water absorption rate was calculated and evaluated based on whether the low water absorption rate could be maintained even under high humidity conditions for a long period of time. For use as an electrical / electronic packaging material, the water absorption rate is preferably low, and is preferably 0.02% or less. [Evaluation Criteria] 1. Test pieces (length 80 mm, width 10 mm, thickness 4 mm) were prepared using an injection molding machine. The test piece was left in an oven at 2.50°C for 24 hours, and then the mass (m1) of the test piece was measured. The test piece was immersed in pure water at 3.23°C for 192 hours, and then the mass (m2) of the test piece was measured. The test piece was left in an oven at 4.50°C for 24 hours, and then the mass (m3) of the test piece was measured. The water absorption rate was calculated according to the following formula. (Water absorption rate [%])=(m2-m3) / m1×100

[0109] <Antistatic properties> The antistatic property was evaluated based on the surface resistivity of the molded article. Using the thermoplastic resin composition, a dumbbell-shaped test piece as described in JIS K7139 (Plastics - Test Piece) was prepared by setting the cylinder temperature of the injection molding machine to 270°C and the mold temperature to 95°C. Using the obtained dumbbell-shaped test pieces, the surface resistivity [Ω / □] of the molded body was measured using a resistivity meter (Hiresta UX MCP-HT800 type resistivity meter, JIS K7194 compliant 4-terminal 4-probe constant current application method, manufactured by Mitsubishi Chemical Analytech Co., Ltd.) (4-terminal probes spaced 0.5 cm apart).

[0110] <Evaluation of mechanical properties of molded products> The mechanical properties were evaluated by an impact test. Using the thermoplastic resin composition, an injection molding machine was used with a cylinder temperature of 270° C. and a mold temperature of 95° C. to produce a molded body having dimensions of 300 mm length×300 mm width×3 mm thickness. The obtained molded article was dropped 20 times from a height of 5 m, and the occurrence of breakage or cracks was confirmed, and the mechanical properties of the molded article were evaluated as follows. [Evaluation Criteria] +++ No breaks or cracks even after 20 drops. (Excellent) ++ Cracks or breaks after 15 drops (Good) + 10 drops will cause cracks or cracks. (OK) NG: Dropping five times will cause breakage or cracks.

[0111] <Cleanliness> An outgassing test and a carbon shedding test were conducted, and the overall cleanliness was evaluated as follows. (Outgassing test) Using the thermoplastic resin composition, a cylinder temperature of an injection molding machine was set to 270° C., a mold temperature was set to 95° C., and a molded body of 300 mm length x 300 mm width x 3 mm thickness was produced and used as a test piece. The outgassing characteristics were measured by collecting the outgassing of the test piece generated when it was heat-treated at 85°C for 60 minutes in an adsorption tube filled with an adsorbent, and measuring it using a GC-MS equipped with a purge and trap device. The outgassing concentration device used was an MSTD-2 58M manufactured by GL Sciences. The outgassing collection conditions were a chamber purge gas flow rate of N2 gas 340mL / min and a collection time of 30 minutes. The analysis method used a GC-MS analyzer, and the analysis conditions were a J&W capillary column DB-5MS column, with the column temperature set to 40°C, held for 3 minutes, then heated to 220°C at a heating rate of 9°C / min for 20 minutes, further heated to 300°C at a heating rate of 10°C / min for 8 minutes, and held at 300°C for 3 minutes. The inlet temperature was set to 280°C. He was used as the carrier gas, with a flow rate of 1.5mL / min and a split ratio of 1:10. The MS analysis (mass analysis) was carried out by the electron ionization method using an analyzer (Agilent HP6890 / 5973-GC / MS). The temperature of the detector was set to 250°C. [Evaluation Criteria] ++ Outgassing less than 5ppm (Excellent) + Outgassing amount is between 5ppm and 10ppm (Good). NG Outgassing amount is 10ppm or more.

[0112] (Carbon shedding test) Using the thermoplastic resin composition, an injection molding machine was used with a cylinder temperature of 270° C. and a mold temperature of 95° C. to produce a molded body having dimensions of 90 mm length×110 mm width×3 mm thickness. The flat surface of the obtained molded article was rubbed 100 times back and forth over a distance of 90 mm using an abrasion tester, with a load (500 g) applied to a piece of PPC paper (50 x 75 mm), and the presence or absence of carbon stains on the paper was visually confirmed.

[0113] [Evaluation Criteria] ++ No carbon shedding observed. + Carbon shedding is faintly visible. NG Carbon loss is observed.

[0114] [Table 2]

[0115] From the above evaluation results, it was confirmed that the thermoplastic resin composition for electrical and electronic packaging materials has excellent electrical conductivity, no in-plane variation, antistatic properties capable of preventing adhesion of dust and dirt, and further suppresses long-term water absorption into the resin composition, and is capable of forming molded articles with excellent moldability. Because of the good interfitting property, it was found that deformation due to residual stress and thermal stress during molding can be suppressed, and it was also confirmed that the composition has excellent moldability. [Explanation of symbols]

[0116] 1. Fitting evaluation test piece 2 Fitting part 3. Fitting evaluation test piece with 1 cm wide insertion part

Claims

1. A thermoplastic resin composition comprising a carbon material and a thermoplastic resin, The carbon material includes carbon nanotubes (A1) and carbon black (A2), The thermoplastic resin includes a cycloolefin polymer (B1) and an elastomer (B2), The carbon nanotube (A1) satisfies the following (1) and (2): The thermoplastic resin composition is characterized in that the molding shrinkage difference ΔT represented by the following formula (I) is 0.10% or less: Thermoplastic resin composition for electrical and electronic packaging materials. Formula (I) ΔT = |T 1 − T 0 | (In formula (I), T 1 is the molding shrinkage rate (%) when the thermoplastic resin composition is injection molded, T 0 is the molding shrinkage rate (%) when cycloolefin polymer (B1) is injection molded. (1) The average diameter is 1 to 50 nm. (2) 1560 to 1600 cm in Raman spectrum -1 Maximum peak intensity G in the range of 1310 to 1350 cm -1 The ratio of the maximum peak intensity D within the range (G / D ratio) is 0.5 to 2.

0.

2. 2. The thermoplastic resin composition for electrical and electronic packaging materials according to claim 1, wherein the total content of the carbon nanotubes (A1) and the carbon black (A2) is 13 mass% or less based on 100 mass% of the thermoplastic resin composition.

3. 2. The thermoplastic resin composition for electrical and electronic packaging materials according to claim 1, wherein the content of the elastomer (B2) is 4 mass% or less based on 100 mass% of the thermoplastic resin composition.

4. 2. The thermoplastic resin composition for electrical and electronic packaging materials according to claim 1, wherein the elastomer (B2) is at least one of an olefin-based elastomer and a styrene-based elastomer.

5. Carbon black (A2) has a BET specific surface area of ​​1000 m 2 The thermoplastic resin composition for electrical and electronic packaging materials according to claim 1, wherein the viscosity is 100 / g or less.

6. 2. The thermoplastic resin composition for electrical and electronic packaging materials according to claim 1, wherein the cycloolefin polymer (B1) has a tensile break strain of 5% or more.

7. A multipurpose test piece A type was molded from the thermoplastic resin composition in accordance with ISO 3167, and then processed in accordance with ISO 2818 to obtain a notched molded body. The Charpy impact strength measured in accordance with ISO 179-1 was 2.0 kJ / m 2 The thermoplastic resin composition for electrical and electronic packaging materials according to claim 1,

8. 2. The thermoplastic resin composition for electrical and electronic packaging materials according to claim 1, wherein a molded article having a thickness of 3 mm formed from the thermoplastic resin composition has a maximum surface height Sz of 50 μm or less.

9. An electrical / electronic packaging material formed from the thermoplastic resin composition for electrical / electronic packaging materials according to any one of claims 1 to 8.

10. Surface resistivity is 1 x 10 4 ~1×10 12 The electrical and electronic packaging material according to claim 9, having a resistance of Ω / □.

Citation Information

Patent Citations

  • Composite material and semiconductor container using the same

    JP2020123720A

  • Substrate housing container

    JP2021150476A

  • Substrate container

    JP6781998B1

  • Polymer blends for microenvironments

    US20230193003A1

  • Alicyclic structure containing polymer resin composition and formed article

    WO2004029152A1